MANFAAT TERAPI SALAT BAGI PECANDU NARKOBA - Rahmatiah, St. Rahmatiah (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2020)
This paper aims to find out the benefits of Salat therapy for drug addicts. The results show that prayer is a physical and psychological therapy for addicts both curative, preventive and constructive, because prayer contains four therapeutic aspects, namely sports aspects, aspects of meditation, aspects of auto-suggestion and aspects of togetherness. The benefits of prayer therapy for drug addicts are very big influence to fortify themselves and eliminate the remaining residual addictive substances in him because every prayer movement contains extraordinary benefits for health both physically and psychologically, as long as the prayer is carried out in accordance with the conditions and harmony, and is done sincerely (sincere), solemn and perfect every movement of prayer.